The Ca2+/Calmodulin-dependent Calcineurin/NFAT Signaling Pathway in the Pathogenesis of Insulin Resistance in Skeletal Muscle - Danowska, Magdalena; Strączkowski, Marek (Experimental and Clinical Endocrinology & Diabetes, 2023)
Skeletal muscle is the tissue directly involved in insulin-stimulated glucose uptake. Glucose is the primary energy substrate for contracting muscles, and proper metabolism of glucose is essential for health. Contractile activity and the associated Ca2+signaling regulate functional capacity and muscle mass. A high concentration of Ca2+and the presence of calmodulin (CaM) leads to the activation of calcineurin (CaN), a protein with serine-threonine phosphatase activity. The signaling pathway linked with CaN and transcription factors like the nuclear factor of activated T cells (NFAT) is essential for skeletal muscle development and reprogramming of fast-twitch to slow-twitch fibers. CaN activation may promote metabolic adaptations in muscle cells, resulting in better insulin-stimulated glucose transport. The molecular mechanisms underlying the altered insulin response remain unclear. The role of the CaN/NFAT pathway in regulating skeletal muscle hypertrophy is better described than its involvement in the pathogenesis of insulin resistance. Thus, there are opportunities for future research in that field. This review presents the role of CaN/NFAT signaling and suggests the relationship with insulin-resistant muscles.
Keywords: CaN/NFAT signaling; glucose uptake; insulin sensitivity